39. REAL SITUATION OF KNOWLEDGE ABOUT FALL PREVENTION FOR PATIENTS OF NURSING STUDENTS AT THAI BINH UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the real situation of knowledge about fall prevention for patients of nursing students at Thai Binh University of Medicine and Pharmacy in 2023.Methods: descriptive cross-sectional study was conducted in 231 sophomore and junior nursing students of Thai Binh University of Medicine and Pharmacy from June 2023 to June 2024Results: The rate of nursing students with general knowledge about preventing falls for patients was 35.1%. Knowledge achieved in each group: risk factors, risk assessment, fall prevention and management were 62,8%, 30,7%, 48,9%, and 47,6% respectively.Conclusions: Nursing students' knowledge about fall prevention for patients is not high. Therefore, fall prevention education programs should be developed and provided to nursing students to ensure accurate knowledge about fall prevention. Additionally, nursing students should be encouraged to use fall risk assessment tools to assess potential fall risk for patients during hospital practice.
Keywords: knowledge; nursing students; fall prevention